Prevalence of Hydatid Cysts in Slaughtered Animals from Elbehera Governorate, Egypt, with a Focus on Histopathology and Molecular Characterization of Camel Cysts - AbouLaila, Mahmoud R.; Anis, Anis; Hamada, Mohamed; Osman, Ahmed E.; Omar, Mosaab A.; Saleh, Nehad Ahmed; Zidan, Sherif; Menshawy, Soad M.; Wheeb, Heba S.; Abdelaziz, Amer R. (Journal of Advanced Veterinary Research, 2023)
Cystic echinococcosis is a worldwide zoonotic infection that triggers significant economic losses in animals. The study’s goal was to reveal the infection with hydatid cysts in animals slaughtered in Elbehera Governorate, Egypt, as well as perform histopathology and molecular characterization of camel cysts using the cox-1 and G1Y162 genes. Elbehera governorate had a total prevalence of 0.35%. Kom-Hamada abattoir had the highest prevalence of 1.7%. Camels had the highest prevalence of 2.17% among the examined animals. Summer had the highest prevalence, at 0.55%. Females had a higher prevalence than males, except for camels. The older animals were infected at a higher rate than the younger ones, except for the buffalo. Location and season had a significant impact on the prevalence, while sex only impacted the prevalence in cattle and buffaloes. The lung had a higher infection than the liver. The cox-1 and G1Y162 genes PCR reactions provided specific DNA bands, and the sequences were for Echinococcus canadensis. The phylogenetic tree of cox-1 indicated that the Egyptian sequence of Elbehera governorate belongs to genotype 6 (G6) of the Echinococcus complex. The sequence shared an identity percentage of up to 99% with previous Egyptian sequences and other E. canadensis in camels from Iran, Mauritania, Algeria, and Sudan. The phylogenetic tree of the G1Y162 protein sequences confirmed that the Egyptian sequence is E. canadensis. Due to the presence of cysts of zoonotic Echinococcus species in slaughtered animals, stringent health regulations are required to prevent infection in animals and humans.